The Perspective of Integrated Protection of Industrial Heritage: A Case Study of Shuanggou Historical Town Protection Planning - Chen, Xie; Ding, Xiaoyu (International Planning History Society Proceedings, 2024)
This article will emphasis on a special kind of industrial heritage, the alcohol-drink industry heritage. Currently, there are 163 sites of the Chinese industrial heritage, most of them are established after 1900s. however, the liquor industry heritages are different with most of industrial heritage that this kind of heritage inherited long history of brewing traditional industry. Meanwhile, the liquor producing mode was transited from manual workshop to modern industry during the modernization upgrades after the founding of New China, and continuing to this day. therefore, the alcohol-drink industry heritage is a witness for development of traditional Chinese industries and represent the characteristics of living heritage. Additionally, due to geographical constraints on alcohol-drink producing, there is used to a close relationship between distilleries and the towns they are located in. This relationship demonstrates how towns promote the clustering of the alcohol industry, and how the distilleries influence on the economic and spatial development of these towns. However, currently, the protection practices of industrial heritage mainly focus on the conservation and utilization of the core items of the heritage, and lack of attention on the relationship between industrial heritage and the surrounding factory towns. In December 2023, the Jiangsu provincial government announced Yanghe town and Shuanggou town as Jiangsu Historical Towns. It shows a perspective of industrial heritage protection extent towards the urban-rural relationships on which these heritages based on, and a discission to protect that kind relationship. Therefore, this article based on the application work for the Jiangsu Historical Town of Shuanggou, and it revaluates the value of the Shuanggou alcohol-drink industry for the development of the town from the perspectives of geographical factors, industrial development transition and distiller-town relationships. And the framework for town protection was constructed by the value.